Measuring Out Life in Coffee Spoons: Canadian Literary Breakfasts - Moyer, Alexia; Cooke, Nathalie (Cuizine)

(untitled) (McGill University Library, 2017)
Two bodies of secondary literature — literary criticism about the appeal of imagined food and food studies analyses of breakfast — identify the potential of this morning meal to establish an aspirational standard. For literary critics, this aspirational standard involves the norms and conventions of the narrative world being staged, which will inevitably come under pressure as the narrative develops. For food writers, this aspirational standard involves nutritional value. Drawing from specific examples in Canadian literature, we argue that it is precisely this aspect of breakfast — as benchmark or standard of measurement — that makes it such a fruitful meal in the writer's narrative toolbox. Literary breakfasts either embody tension and conflict, or set up and therefore contain the germs of tension and conflict that will drive the plot.